Принципи правового регулювання трудової діяльності авіаційного персоналу державної авіації України - Бершадська, Ю. В.; Bershadska, Yu. V. (Науковий часопис НПУ імені М. П. Драгоманова. Серія 18 : Право. - 2023. - Вип. 39. - С. 10-15, 2023)
Розкрито зміст, сутність принципів правового регулювання трудової діяльності авіаційного персоналу в державній авіації, розглянуто їх особливості. Визначено загальні і спеціальні принципи правового регулювання.

The article is devoted to theoretical research and legal analysis of such a category as the principles of legal regulation of labor activity of aviation personnel of state aviation. The relevance of the study is determined by the need to build a legal state, the establishment of the constitutional principle of the rule of law, and the provision of real, legislative implementation of the labor rights of specialists in the aviation industry. In the current regulatory acts, there is no legislative consolidation of the concept of "principles of legal regulation of the labor activity of aviation personnel of state aviation", since even such fundamental legal categories as "principles of law", "principles of labor law", "principles of legal regulation of labor relations" are not legally established. These concepts have both theoretical and practical significance, since the principles themselves act as social guidelines that form the foundation for the regulation of a certain type of social relations, in particular, the labor relations of the aviation personnel of the state aviation. The theoretical study of the discussed topic was conducted for the first time and is conditioned by the special role and performance of specific functions of the aviation personnel of the state aviation, which consist in ensuring the national security and defense of the state, as well as the protection of the population. During the performance of professional duties by specialists of the aviation personnel of the state aviation, there are undoubtedly special social relations regarding the realization and protection of the labor rights of the personnel, which require legislative regulation. The principles of legal regulation of the labor activity of aviation personnel in the state aviation system have their own characteristics and certain objective signs, in the presence of which the differentiation of legal regulation of labor relations is carried out. This determines the objective necessity of regulating these relations by general norms of the general and special regulatory acts, which allows implementing a differentiated approach to the legal regulation of labor.

Раскрыты содержание, сущность принципов правового регулирования трудовой деятельности авиационного персонала в государственной авиации, рассмотрены их особенности. Определены общие и специальные принципы правового регулирования.
Principles of legal regulation of labor activities of the aviation personnel of the state aviation of Ukraine
Keywords: правове регулювання; legal regulation; правовое регулирование; державна авіація; state aviation; государственная авиация; трудова діяльність; employment; трудовая деятельность; авіаційний персонал; aviation personnel; авиационный персонал; принципи; principles; принципы; трудові відносини; labor relations; трудовые отношения